2021
DOI: 10.1016/j.vaccine.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID-19 vaccination intention using protection motivation theory and conspiracy beliefs

Abstract: Background While COVID-19 vaccine uptake has been encouraging overall, some individuals are either hesitant towards, or refuse, the vaccine. Protection Motivation Theory (PMT) has been applied to influenza vaccine acceptance, but there is a lack of research applying PMT to COVID-19 vaccine acceptance. Additionally, prior research has suggested that coronavirus conspiracy beliefs and demographic factors may play a role in attitudes towards the vaccine. This study aimed to predict COVID-19 vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
3
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 18 publications
10
78
3
7
Order By: Relevance
“…Consistently with previous studies, results showed that a high perception of risk related to COVID-19 predicts the intention to vaccinate against it 25 , 45 and, to a much greater extent, to accept CTAs 17 , 18 , 21 , 22 . These result are in line with different models, such as the Risk as Feeling Model, according to which feelings and emotions about a specific situation influence people’s behavior who attach an emotional value to a specific situation 46 , or the Protection Motivation Theory, according to which people are motivated to respond to health threats engaging in protective behaviors 47 , 48 . As previously mentioned, COVID-19 related fear, worry, and uncertainty have been found to enhance the adoption of CTAs as measures to help control the spread of the disease 17 , 18 , 21 , 22 .…”
Section: Discussionsupporting
confidence: 78%
“…Consistently with previous studies, results showed that a high perception of risk related to COVID-19 predicts the intention to vaccinate against it 25 , 45 and, to a much greater extent, to accept CTAs 17 , 18 , 21 , 22 . These result are in line with different models, such as the Risk as Feeling Model, according to which feelings and emotions about a specific situation influence people’s behavior who attach an emotional value to a specific situation 46 , or the Protection Motivation Theory, according to which people are motivated to respond to health threats engaging in protective behaviors 47 , 48 . As previously mentioned, COVID-19 related fear, worry, and uncertainty have been found to enhance the adoption of CTAs as measures to help control the spread of the disease 17 , 18 , 21 , 22 .…”
Section: Discussionsupporting
confidence: 78%
“…A broader literature has also shown that vaccination against COVID-19 was politicized, and belonging to a political party might affect individuals' decision making for vaccina-tion [30,63]. Conspiracy beliefs also play an important role in persons being reluctant to undergo vaccination [66].…”
Section: Discussionmentioning
confidence: 99%
“…Current research into COVID-19 vaccine hesitancy has explored attitudes and beliefs related to COVID-19 vaccine hesitancy. [13][14][15] Conspiracy beliefs also occur in a significant minority and are linked to lower adherence to coronavirus government guidelines and a lower willingness to take coronavirus tests or get vaccinated. 5,7 While it is important to uncover psychological factors underpinning COVID-19 vaccine hesitancy, 16 most studies are quantitative.…”
Section: Background Of the Studymentioning
confidence: 99%